Intelligent transportation systems: prospects, effectiveness, and challenges - Arseniy A. Efimov; Kseniya S. Medvedeva (International Journal of Advanced Studies)
Background. Intelligent transport systems (ITS) represent one of the most significant and relevant topics in the field of modern transport and logistics. With the rapid growth of the urban population, an increase in freight traffic and a constant increase in the number of cars on the roads, the need for efficient and reliable transport solutions is becoming more and more obvious. ITS, as a set of technologies and methods aimed at optimizing transport processes, can significantly improve the efficiency of transport systems, improve road safety and reduce the negative impact on the environment.